Characterization of Hydraulic Fluids and Development of Heat Transfer Correlation in Helical Coil using New Dimensionless Number M - Pawar, SS; Sachin K, Kamble (International Journal of Computer Sciences and Engineering, 2025)
The heat transfer rate in helical coils is higher than in straight tube due to secondary motion developed. The characterization of fluid flow in helical coil is very difficult due to complex flow pattern. In this experimental work, an innovative approach for the characterization of fluid flow and development of heat transfer correlations in helical coil for Newtonian fluids using new dimensionless Number M is presented. Experiments were conducted under isothermal and non-isothermal conditions for the development of innovative heat transfer correlations. Three helical coils of different coil curvature ratios are used in this work. The innovative correlations were validated using work of earlier investigators and are found to be satisfactory.